2007
DOI: 10.1021/bi062264p
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallographic and Biochemical Characterization of the Inhibitory Action of an Imidazole−Dioxolane Compound on Heme Oxygenase,

Abstract: Heme oxygenase (HO) catalyzes the regiospecific cleavage of the porphyrin ring of heme using reducing equivalents and O2 to produce biliverdin, iron, and CO. Because CO has a cytoprotective effect through the p38-MAPK pathway, HO is a potential therapeutic target in cancer. In fact, inhibition of the HO isoform HO-1 reduces Kaposi sarcoma tumor growth. Imidazole-dioxolane compounds have recently attracted attention because they have been reported to specifically inhibit HO-1, but not HO-2, unlike Cr-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 37 publications
(47 reference statements)
5
54
0
Order By: Relevance
“…The potency of this compound was very similar to that of QC-1 (6 + 1 mM) for HO-1, but removal of the bulky 4-aminophenylthiol groups in the northeastern region resulted in decreased activity towards HO-2 in comparison with QC-1 whose IC 50 was 28 + 18 mM. This compound was also the first to be crystallized, as reported by Sugishima et al [76], in complex with rat HO-1 (rHO- 77]. The similarity in inhibitory effect was quite interesting, given the structural differences between these two compounds.…”
Section: A Common Binding Mode For Imidazole-based Heme Oxygenase-1 Isupporting
confidence: 70%
See 2 more Smart Citations
“…The potency of this compound was very similar to that of QC-1 (6 + 1 mM) for HO-1, but removal of the bulky 4-aminophenylthiol groups in the northeastern region resulted in decreased activity towards HO-2 in comparison with QC-1 whose IC 50 was 28 + 18 mM. This compound was also the first to be crystallized, as reported by Sugishima et al [76], in complex with rat HO-1 (rHO- 77]. The similarity in inhibitory effect was quite interesting, given the structural differences between these two compounds.…”
Section: A Common Binding Mode For Imidazole-based Heme Oxygenase-1 Isupporting
confidence: 70%
“…Comparison of the structures of the two inhibitor -HO-1 complexes revealed a common binding mode for these seemingly structurally distinct, imidazole-based compounds (figure 4a,b) [76,77]. While it appears that the inhibitors bind within the heme-binding pocket, they do not displace and rather require the heme moiety for binding, which explains the non-competitive nature of the inhibition as determined through kinetic analyses.…”
Section: A Common Binding Mode For Imidazole-based Heme Oxygenase-1 Imentioning
confidence: 95%
See 1 more Smart Citation
“…Zinc-protoporphyrin was developed to treat cancer (Fang et al, 2004b). Recently, imidazole-dioxolane compounds have been shown to act as inhibitors of HO activity (Vlahakis et al, 2006;Sugishima et al, 2007) and shown to be effective as inhibitors of specific HO isoenzymes as well as HO activity (Kinobe et al, 2007).…”
Section: B Heme Oxygenase Isozymesmentioning
confidence: 99%
“…The tetrazoles exhibited less effect than the 1,2,4-triazoles, which in turn exerted less effect than their imidazole-containing counterparts. Previous work detailing the cocrystallization of HO-1 with QC-15 (Sugishima et al, 2007;Rahman et al, 2008), QC-82 (Rahman et al, 2008), and QC-86 bound (Roman et al, 2010) demonstrated that the imidazole and 1,2,4-triazole pharmacophore coordinated with the heme iron through the N3 atom in the azole ring. It is possible that the heme in the P450 active site coordinates with the HO inhibitors in a similar fashion and that, with each additional nitrogen in the five-membered ring, the displaced charge on each nitrogen in the three and/or four position results in a compound that is less tightly bound to the heme in the P450 active site and could thus be more easily displaced by the substrate, leading to decreased P450 inhibition.…”
Section: Discussionmentioning
confidence: 99%